Implications of Software Testing Strategies at Initial Level of CMMI: An Analysis - Sharma, R; Dadhich, R (International Journal of Computer Sciences and Engineering, 2025)
Software Testing is an essential and important phase of SDLC. The quality and acceptance of any software highly depends on the success of software testing phase. The successful completion of testing phase also ensures that the produced software is of good quality. In order to achieve high quality product lots of Process Maturity Models have been developed and CMMI is one of the most popular among them. The organizations at the initial level of CMMI (also non-CMMI compliance organizations) neither implement any of the standard processes for software product development nor they use any software testing strategies, hence, the quality of the product produced by them is always susceptible and imposes a great risk over its acceptance as well as on their survival. The main driving force behind this paper is to study the implications of software testing processes (partially or at introductory level) over the quality of software produced by the organizations at initial level.